REVITALISASI BATIK GAMBO SEBAGAI WARISAN BUDAYA MUSI BANYUASIN MELALUI PEMANFAATAN LIMBAH GAMBIR - Dwi Ulfa S; Wasino; Kurniawan E; Aricindy A; Suryadi (STKIP Subang, 2026)
This study aims to synthesize key findings regarding the potential and urgency of revitalizing Gambo Batik in Musi Banyuasin (Muba) through the integration of gambier waste utilization as a natural dye. Gambo Batik, which faces challenges in dyeing sustainability and market competitiveness, can gain competitive advantage and authentic value through this circular economy approach. Based on literature analysis related to the advantages of tannin dyes in gambier waste, the challenges of preserving Gambo Batik, and the waste-based creative economy development model, this review concludes that the utilization of gambier waste is a strategic solution. This solution not only offers ecological sustainability and strengthening cultural identity, but also opens new opportunities for the economic well-being of Muba artisans by converting waste costs into product added value.